PEMBELAJARAN TRANSFORMATIF DEWASA DI ERA DIGITAL: REKONSTRUKSI IDENTITAS MELALUI PENGALAMAN BELAJAR VIRTUAL - Audrey Nabila Firmansyah Putri; Nurlaela Hamidah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Transformative learning in the digital era has become essential for adult learners, yet comprehensive understanding of its intellectual landscape remains limited. This study maps the intellectual landscape of transformative learning in digital-era adult education psychology and identifies research trends and conceptual clusters. A systematic literature review combined with bibliometric analysis examined 58 peer-reviewed publications from 2021-2025 across Scopus, Web of Science, Education Resources Information Center, and Google Scholar. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 protocols, data were analyzed using VOSviewer to generate network, overlay, and density visualizations through co-occurrence analysis. Results revealed three primary clusters: pedagogical dimensions emphasizing educator roles across diverse contexts; organizational relevance for leadership development; and pandemic-driven digitalization creating digital divide challenges. Findings demonstrate that digital-era transformative learning represents a multidimensional phenomenon integrating technological, pedagogical, psychological, and socio-cultural factors, providing critical foundation for equitable adult education practices. ABSTRACT Transformative learning in the digital era has become essential for adult learners, yet comprehensive understanding of its intellectual landscape remains limited. This study maps the intellectual landscape of transformative learning in digital-era adult education psychology and identifies research trends and conceptual clusters. A systematic literature review combined with bibliometric analysis examined 58 peer-reviewed publications from 2021-2025 across Scopus, Web of Science, Education Resources Information Center, and Google Scholar. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 protocols, data were analyzed using VOSviewer to generate network, overlay, and density visualizations through co-occurrence analysis. Results revealed three primary clusters: pedagogical dimensions emphasizing educator roles across diverse contexts; organizational relevance for leadership development; and pandemic-driven digitalization creating digital divide challenges. Findings demonstrate that digital-era transformative learning represents a multidimensional phenomenon integrating technological, pedagogical, psychological, and socio-cultural factors, providing critical foundation for equitable adult education practices. ABSTRAK Pembelajaran transformatif di era digital adalah hal yang penting untuk pembelajar dewasa, namun pemahaman komprehensif tentang lanskap intelektualnya masih terbatas. Penelitian ini memetakan lanskap intelektual pembelajaran transformatif dalam psikologi pendidikan orang dewasa di era digital serta mengidentifikasi tren penelitian dan cluster konseptual. Systematic literature review dikombinasikan dengan analisis bibliometrik mengkaji 58 publikasi peer-reviewed dalam periode 2021-2025 dari Scopus, Web of Science, Education Resources Information Center, dan Google Scholar. Mengikuti protokol Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020, data dianalisis menggunakan VOSviewer untuk menghasilkan visualisasi network, overlay, dan density melalui analisis co-occurrence. Hasil mengungkapkan tiga cluster utama yaitu, dimensi pedagogis yang menekankan peran pendidik dalam konteks beragam, relevansi organisasional untuk pengembangan kepemimpinan, serta digitalisasi akibat pandemi yang menciptakan tantangan kesenjangan digital. Temuan penelitian ini menunjukkan pembelajaran transformatif era digital merupakan fenomena multidimensional yang mengintegrasikan faktor teknologis, pedagogis, psikologis, dan sosio-kultural, memberikan fondasi kritis untuk praktik pendidikan orang dewasa yang ekuitas.